UTILIZATION OF SOCIAL MEDIA IN QUR'AN LEARNING: A SYSTEMATIC STUDY OF POTENTIAL, RISKS, AND USAGE STRATEGIES - Suwardi, Suwardi; Nuradilah, Nuradilah; Riyadi, Slamet (Journal of Social and Economics Research, 2025)
Digital transformation has brought significant changes to Quranic learning methods, including through the use of social media such as YouTube, Instagram, and TikTok. This study aims to systematically examine the potential, risks, and strategies for using social media in Quranic learning. The methods used are:Systematic Literature Review(SLR) using the PRISMA approach, which analyzed 35 articles published between 2018 and 2024 from the Scopus, Google Scholar, and Web of Science databases. The results show that social media has the potential to expand access to learning, strengthen learning communities, and increase the motivation of the younger generation through interactive approaches. However, risks were also identified, including the spread of invalid content, weakened scientific authority, and digital distractions. The literature recommends teacher training, collaboration with content creators, and a curriculum based on sanad and digital. This study emphasizes the importance of a structured strategy to make social media an effective means of learning the Quran while remaining grounded in scientific and spiritual values.